ESG REPORTING IN ROMANIA: ASSESSING SUSTAINABILITY PRACTICES AND THEIR FINANCIAL IMPACT ON BET-LISTED COMPANIES - Raul-Constantin BUCUREAN; Roxana-Nadina BUCUREAN (ROIBAN) (Oradea Journal of Business and Economics, 2025)
In recent years, ESG reporting in Romania has gained increasing relevance, driven by both regulatory developments at the European level and growing investor demand for transparency regarding corporate sustainability practices. This paper investigates the development and implementation of Environmental, Social, and Governance (ESG) initiatives among companies listed on the Bucharest Stock Exchange (BET 20 index), based on the analysis of their 2023 sustainability reports. The research aims to evaluate both the level of ESG reporting maturity and the extent to which ESG performance is associated with financial outcomes, particularly EBITDA. To examine the financial implications of ESG performance, a quantitative analysis was conducted using multiple linear regression. The results indicate a statistically significant and positive correlation between the Social (S) score and EBITDA, suggesting that companies with stronger social engagement—such as employee welfare, community involvement, and health and safety practices—may benefit from improved financial performance. Conversely, the Environmental (E) and Governance (G) scores did not exhibit statistically significant relationships with EBITDA, although the Governance component showed a moderate negative trend, potentially reflecting short-term costs associated with compliance and reform initiatives. The findings underscore the potential for ESG, particularly the Social dimension, to act as a driver of financial value in the Romanian market context. However, the heterogeneity of ESG reporting practices suggests the need for greater standardization and regulatory alignment. This study contributes to the limited empirical literature on ESG in Eastern Europe and provides practical implications for policymakers, investors, and corporate leaders seeking to integrate sustainability considerations into financial decision-making.